Al-Qur’an sebagai Handbook dalam Mengenal dan Mengelola Alam - Rahayu Fuji Astuti; Meity Ummiyah; Mutiah Rahmadhani Hasibuan (Jurnal Semiotika Quran, 2024)
This research aims to reveal the miraculous verses of the Qur'an as a book of guidance and guidance for humans and provide benefits both theoretically and practically. Theoretically, this research is expected to be able to provide additional new references and references for further research. Practically, this research is able to provide benefits to humans and make one of the guidelines for daily life, especially in managing nature. This research method uses the type of literature with descriptive analytical data analysis techniques. The results of this study reveal that the evidence of the miracle of the Qur'an which is examined by scientists about the truth of the Qur'an and leads all scientists to the gate of Islam, becomes strong to be used as a Muslim handbook. The Qur'an as a guide in recognizing and managing nature is also concrete evidence of its authenticity and originality as the holy book of Muslims.